Efficient rate enhancement due yo intramolecular general base (IGB) assistance in the hydrolysis of N-(O-Hydroxyphenyl)Phthalimide - Ariffin, Azhar; Khan, M.N.; Sim, Y.L. (2007)
The rates of the hydrolyses of N-(o-hydroxyphenyl)phthalimide (1) and N-(o-methoxyphenyl)phthalimide (2), studied at different pH, show that the hydrolysis of 1 involves intramolecular general base (IGB) assistance where the o-O- group of ionized 1 acts as IGB and H2O as the reactant. The rate enhancement due to the IGB-assisted reaction of H 2O with ionized 1 is >8 × 104-fold. Pseudo-first-order rate constant for the reaction of water with 2 is ∼2 × 103-fold smaller than the first-order rate constant (0.10 s-1) for pH-independent hydrolysis of 1 within the pH range of 9.60-10.10. Second-order rate constants (kOH) for hydroxide ion-assisted hydrolysis of ionized 1 and 2 are 3.0 and 29.1 M-1 s-1, respectively. The solvent deuterium kinetic isotope effect (dKIE) on the rate of alkaline hydrolysis of 1 and 2 reveals that the respective values of kOH/kOD are 0.84 and 0.78, where kOD represents the second-order rate constant for DO--assisted cleavage of these imides (1 and 2). The value of kwH2O/k dD2O is 2.04, with kwH2O and k dD2O representing pseudo-first-order rate constants for the reactions of ionized 1 with H2O and D2O, respectively. © 2007 American Chemical Society.